O ensino da astronomia nos anos iniciais do ensino fundamental: implicações no processo de ensino e aprendizagem - Santos , Elizandra Daneize dos (2022)
The school has an important role in society, with the purpose of developing the intellectual capacity of students, mediating the knowledge systematically elaborated and promoting the development of theoretical thinking through teaching and learning processes. Among the contents worked in the school context, we highlight Astronomy, an area of knowledge inserted in the curriculum of the Science discipline, whose scientific contents seek to explain the astronomical phenomena that are observed in everyday life. The general objective of this research is to investigate the approach of astronomy contents of the Science discipline in the Municipal Schools of Medianeira, as well as its implication in the teaching and learning process in the Early Years of Elementary School. We have delimited the objectives based on the following problem: is there an approach to the contents of Astronomy in the classrooms of the Municipal Schools of Medianeira and, and if there is, how does it occur? The methodological perspective is permeated by the mixed approach (qualitative and quantitative), based on Bardin's Content Analysis. Its theoretical construction is carried out with bibliographic research in books, articles, dissertations and theses, contained in libraries and online databases. To verify the hypothesis, a field search was performed. Data collection is effective with the application of questionnaires developed by the researchers themselves, directed to the Municipal Department of Education, the principals/coordinators of the schools and the teachers of Science of the Early Years of Elementary School, obtaining the participation of 56 volunteers. Data analysis presents the results obtained and tabulated in order to analyze and discuss the aspects that influence the teaching and learning process of astronomy contents. With the results, we established reflections on the training of education professionals, which needs to be rethought and resignified, inquiring about the problems that permeate the teaching of this content in the practice of the classroom, and thus establish important contributions to research in Science and Astronomy teaching. We found that the lack of Astronomy teaching in the initial and continuing education of teachers results in difficulties related to the elaboration of classes and understanding of the contents, as well as it causes instability, doubts and insecurity that interfere in the development of methodological proposals that promote the abstraction of contents and help in the teaching and learning process.